Abrasively modified electrodes: mathematical modelling and numerical simulation of electrochemical dissolution/growth processes under cyclic voltammetric conditions - Chevallier, F; Goodwin, A; Banks, C; Jiang, L; Jones, T; Compton, R (2006)
An approximate mathematical model for electrochemical dissolution/growth processes of diffusionally independent and well-separated particles randomly dispersed on an inert conducting electrode surface is presented and solved using numerical simulation. The model, mimicking abrasively modified electrodes where particles of electroactive voltammograms solid are immobilised on an electrode surface, provides clear insights into the effects of different parameters on the voltammetric response of such systems and permits the exploration of the competition taking place between mass transport and surface processes. The mathematical model is then compared with experimental data obtained with basal plane pyrolytic graphite electrode abrasively modified with solid particles of perinaphthenone and studied in aqueous solution.